Studio sulla contaminazione ambientale delle acque causata dall'escrezione umana dei farmaci - Calà, Piergiuseppe (Scuole di dottorato, 2007)
The use of substances for pharmaceutical use, either as disinfectants or used clinically for diagnostic purposes, cosmetic products or personal hygiene, is widespread in all areas of daily and working life. Recently, the research on environmental contamination caused by PPCPs (Pharmaceuticals and Personal Care Products) has been focused on the consequences deriving from the dispersion of antibiotic or hormonal substances, in relation to the phenomenon of the increase in bacterial resistance and to interference on the endocrine systems respectively. The research described in this volume is part of the national and international studies on the problem, aims at contributing in the expansion of knowledge on these themes and has as its objective the determination of the possible presence of drug residues in the Arno river.